PARP1 controls KLF4-mediated telomerase expression in stem cells and cancer cells. Issue 18 (1st August 2017) - Hsieh, Meng-Hsun; Chen, Yi-Ting; Chen, You-Tzung; Lee, Yi-Hsuan; Lu, Jean; Chien, Chung-Liang; Chen, Hsin-Fu; Ho, Hong-Nerng; Yu, Chia-Jung; Wang, Zhao-Qi; Teng, Shu-Chun
Abstract: Telomerase is highly expressed in cancer and embryonic stem cells (ESCs) and implicated in controlling genome integrity, cancer formation and stemness. Previous studies identified that Krüppel-like transcription factor 4 (KLF4) activates telomerase reverse transcriptase (TERT) expression and contributes to the maintenance of self-renewal in ESCs. However, little is known about how KLF4 regulates TERT expression. Here, we discover poly(ADP-ribose) polymerase 1 (PARP1) as a novel KLF4-interacting partner. Knockdown of PARP1 reduces TERT expression and telomerase activity not only in cancer cells, but also in human and mouse ESCs. Recruitment of KLF4 to TERT promoter is reduced in PARP1-suppressed cells. The poly(ADP-ribose) polymerase activity is dispensable, while the oligo(ADP-ribose) polymerase activity is required for the PARP1- and KLF4-mediated TERT activation. Repression of Parp1 in mouse ESCs decreases expression of pluripotent markers and induces differentiation. These results suggest that PARP1 recruits KLF4 to activate telomerase expression and stem cell pluripotency, indicating a positive regulatory role of the PARP1–KLF4 complex in telomerase expression in cancer and stem cells.